Singuläre Störungsrechnung: 29.05. - 04.06.1994 - Jäger, Willi; Modica, Luciano; Hale, Jack K. (Tagungsbericht, 1994)
Ulrich Hornung; Olga A. Oleinik; Nicholas D. Alikakos; Peter W. Bates; Giovanni Bellettini; Pavol Brunovsky; Jack Carr; Gregory A. Chechkin; Francine Diener; Marc Diener; Paul C. Fife; Martin Flucher; Giorgio Fusco; Rustem R. Gadyl'shin; Steffen Heinze; Willi Jäger; Xiao-Biao Lin; Stephan Luckhaus; Andro Mikelic; Stefan Müller; Nikolai Nefedov; Maria Neuss-Radu; Robert E. O'Malley, Jr.; Jeannine Saint Jean Paulin; Björn Sandstede; Klaus R. Schneider; Daniel Sevcovic; Alexei Shamaev; Pavel E. Sobolevskii; Uwe Stroinski; Luc Tartar; Ping J. Xun; Wen-an Yong